Battery Electrodes: Fabrication of Low‐Tortuosity Ultrahigh‐Area‐Capacity Battery Electrodes through Magnetic Alignment of Emulsion‐Based Slurries (Adv. Energy Mater. 2/2019). Issue 2 (9th January 2019) - Li, Linsen; Erb, Randall M.; Wang, Jiajun; Wang, Jun; Chiang, Yet‐Ming
Abstract : In article number1802472, Yet‐Ming Chiang and co‐workers use magnetically aligned Fe3 O4 containing oil droplets as pore formers to produce highly oriented, low‐tortuosity pore channels that address transport limitations of thick electrodes (>400 μm thickness) with ultrahigh areal capacity (≈14 mAh cm −2 versus 2–4 mAh cm −2 for conventional Li‐ion). This method opens new opportunities for developing high energy‐density or fast charging low‐cost batteries based on thick electrodes.